1997
DOI: 10.1128/jvi.71.7.5003-5011.1997
|View full text |Cite
|
Sign up to set email alerts
|

Multiple extracellular domains of CCR-5 contribute to human immunodeficiency virus type 1 entry and fusion

Abstract: Human immunodeficiency virus type 1 (HIV-1) entry is governed by the interaction of the viral envelope glycoprotein (Env) with its receptor. The HIV-1 receptor is composed of two molecules, the CD4 binding receptor and a coreceptor. The seven-membrane-spanning chemokine receptor CCR-5 is one of the coreceptors used by primary isolates of HIV-1. We demonstrate that the mouse homolog of CCR-5 (mCCR-5) does not function as an HIV-1 coreceptor. A set of chimeras of human CCR-5 and mCCR-5 was studied for Env-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 88 publications
(123 reference statements)
2
45
1
1
Order By: Relevance
“…We believe that the results of our analyses of human/NIH/ Swiss mouse CCR5 chimeras are fully compatible with related evidence from other laboratories which have also implicated the amino terminus and extracellular loops 1 and 2 of human CCR5 in infections by macrophage-tropic HIV-1 (4,8,34,38). However, as discussed elsewhere (8,34), the earlier studies did not give identical results, presumably because the reference proteins, viruses, cell lines, assay methods, and chimera splice sites were distinct. For example, several of these studies used syncytium rather than infection assays, epitope-tagged rather than native CCR5s, or coreceptor overexpression in COS-7 cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We believe that the results of our analyses of human/NIH/ Swiss mouse CCR5 chimeras are fully compatible with related evidence from other laboratories which have also implicated the amino terminus and extracellular loops 1 and 2 of human CCR5 in infections by macrophage-tropic HIV-1 (4,8,34,38). However, as discussed elsewhere (8,34), the earlier studies did not give identical results, presumably because the reference proteins, viruses, cell lines, assay methods, and chimera splice sites were distinct. For example, several of these studies used syncytium rather than infection assays, epitope-tagged rather than native CCR5s, or coreceptor overexpression in COS-7 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of these CCR5 clones suggested that SIV mac251 interacts differently than all tested macrophage-tropic HIV-1 isolates with position 14 in the amino terminus of CCR5, with position 93 in extracellular loop 1, and with extracellular loop 2. Our chimera results differ in several respects from those of other studies (4,8,34,38), in part because the NIH/Swiss mouse CCR5 contains a unique amino acid substitution in extracellular loop 2 that is nonpermissive for HIV-1 infections. We have identified amino acids in three extracellular regions of CCR5 that appear to be critical for HIV-1 coreceptor function.…”
contrasting
confidence: 98%
See 1 more Smart Citation
“…Because minimal changes in membrane fluidity are logarithmically responsible for infectivity [15], it is plausible that a reduction of fluidity by GL is the primary mechanism causing inhibition of viral infectivity. It has been proposed that membrane and envelope fluidities play a pivotal role in the formation of the wide fusion pore of enveloped viruses, by clustering a substantial number of activated viral fusion proteins derived from multiple ligand-receptor complexes [39][40][41][42][43]. In this respect, GL mainly acts against enveloped viruses.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the hypothesis that dual tropism may arise by acquisition of the ability to use ECL1 and 2 of CXCR4, while retaining the ability to use the CCR5 N-terminus (61). We and others have noted that R5X4 strains are more sensitive to disruption of CCR5 structure than R5 strains (64,65). In addition, a number of R5X4 HIV-1 strains are markedly more sensitive than R5 strains to RANTES inhibition on cell lines expressing CCR5 (Fig.…”
Section: Progression From Ccr5 To Cxcr4 Usagementioning
confidence: 96%